2017
DOI: 10.1177/1010428317695013
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on immune checkpoint inhibitors in non–small cell lung cancer

Abstract: The treatment of advanced or refractory non-small cell lung cancer has been historically difficult owing to the lack of studies on effective systemic cure. The progress in lung cancer treatment has plateaued, necessitating new options for additional benefits. Immune checkpoint proteins are co-inhibitory factors that can diminish the antigen-specific immune responses by attenuating the regulatory role of cytotoxic T-lymphocyte-associated protein 4, programmed cell death-1, lymphocyte-activation gene 3, and T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…[21][22][23][24] IL-6, an important signal stimulating factor in lung cancer immunization, is closely related to the occurrence and poor prognosis of lung cancer. 25 In the current study, we found that the expression of IL-6 and GP130 was significantly high (Table 1) and was associated with poor prognosis in NSCLC ( Figure 2). The IL-6 expression has also been associated with NSCLC tumor size.…”
Section: Discussionsupporting
confidence: 49%
“…[21][22][23][24] IL-6, an important signal stimulating factor in lung cancer immunization, is closely related to the occurrence and poor prognosis of lung cancer. 25 In the current study, we found that the expression of IL-6 and GP130 was significantly high (Table 1) and was associated with poor prognosis in NSCLC ( Figure 2). The IL-6 expression has also been associated with NSCLC tumor size.…”
Section: Discussionsupporting
confidence: 49%
“…It is clear that in NCLC, several immune checkpoint pathways are expressed simultaneously and are correlated as a major mechanism of immune resistance against T cell response. 23,24 Indeed, we showed that MCs can express more than one checkpoint marker at the same time; in this regard, using sequential staining of our markers, we observed 11 simultaneous or unique expression patterns of PD-L1, B7-H3, B7-H4, and IDO-1 by MCs. Furthermore, we identified that PD-L1 þ B7-H3 þ IDO-1 was the most common combination simultaneously expressed by MCs in ADCs and PD-L1 þ B7-H3, and B7-H3 þ B7-H4 were the most common combinations in SCCs, suggesting that lung tumors can use preferentially more than one pathway to evade the immune system.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with previously published work by Ngiow et al (30), we observed that a decreased frequency of PD-1 + CD8 + TILs corresponded with an increased efficacy of anti-PD-1 therapy. However, to date, definitive data regarding PD-1 expression on CD8 + TILs and how this impacts responses to anti-PD-1 is debatable (6). Moreover, our data regarding PD-1 expression on CD8 + TILs is observational and warrants further investigation to more definitively evaluate if low PD-1 expression on CD8 + TILs in our model is directly linked to increased anti-PD-1 efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite remarkable and durable responses, long term control of tumors is achieved in only a fraction of patients. Extensive pre-clinical and clinical studies to identify the differences between responders and nonresponders demonstrate a lack of anti-tumor T cell activity within the tumor microenvironment (TME) of non-responders (36). Multiple lines of evidence indicate that checkpoint inhibitors are more effective in combination with treatments that generate a robust CD8 + T cell infiltrate, including radiation (7), chemotherapy (8), and immune activating agents (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation